Millennial Women and The Paradigm Shift of Religiosity: a Case Study in an Urban Community - Tanamal, Nini Adelina (MSJ : Majority Science Journal, 2024)
This study adopts a library research method to analyze the paradigm shift of millennial women’s religiosity in urban society. Through the exploration of relevant literature on religiosity, urbanization, technology, and gender dynamics, this research seeks to understand how millennial women adapt their religious beliefs and practices in the context of modern life. The main findings of this study show that millennial women in urban environments are starting to shift from traditional religiosity to a more personal, flexible, and more suitable form of religiosity that suits their contemporary lifestyle. This shift is influenced by a number of factors, including urbanization that causes changes in the social environment, technological advancements that facilitate access to information and interaction, and the influence of social media that allows women to shape and spread their own narratives of religiosity. In addition, the demands of gender roles also play an important role in how millennial women navigate their religious lives amid various social and family responsibilities. Millennial women not only function as recipients of religious values, but also as agents of change who are active in shaping and updating religious practices that are more inclusive and relevant to the challenges of the times. Thus, this study not only makes a theoretical contribution to the understanding of millennial women’s religiosity, but also opens up opportunities for further empirical research to delve deeper into the dynamics of religiosity in urban society.